Crianças do bairro-comunidade Jarumã Abaetetuba-PA: sobre significados, cotidianos e a cultura do lugar - SANTOS, Gizelma Dias dos (2024)
The present work deals with the knowledge of children from the neighborhoodcommunity Jarumã, focusing on the child-place-culture tripod, considering their meanings, games and socializing in the daily life of these subjects. We reflect on children in order to understand the heterogeneous processes culturally produced by children's subjects in the perspective of giving visibility to their concrete life. For this, we resorted to authors Brandão (2015, 2007, 1997), Pojo (2017), among others; yet another empirical essay based on the assumptions of ethnography, using observation, photographic records and interviews with children and adults living in the jarumã neighborhood-community. As a result, we point out that the children of this neighborhood-community have knowledge immersed in their own Amazonian children's world. Also, children are governed by the local culture, which concerns actions, language, everyday rules, etc. Knowledge that is taught and transmitted within the local culture and the little ones, and thus captures a way of life lived in dialogue with the adult. Finally, there is the exception of the importance of all this to the school for the construction of subjects.